The specificity of acute and chronic microvascular alterations in renal allografts. (1st October 2013) - Filippone, Edward J.; Farber, John L.
Abstract The diagnosis of an antibody‐mediated rejection (AMR) is made when there is evident histologic injury in the presence of detectable donor‐specific alloantibodies (DSA) and diffuse peritubular capillary C4d staining (C4d‐pos). In the presence of only detectable DSA or C4d‐pos, the tissue injury is currently considered "presumptive" for antibody causation. In acute antibody‐mediated rejection (AAMR), diagnostic morphologic features include microvascular inflammation (MVI), specifically glomerulitis and peritubular capillaritis. In the case of chronic active AMR (CAAMR), these inflammatory lesions have progressed to chronic microvascular injury, transplant glomerulopathy (TG) and peritubular capillary basement membrane multilayering (PTCBMML). Either TG or PTCBMML is sufficient morphological evidence for a diagnosis of CAAMR. Unfortunately, these lesions are not specific. MVI, TG, and PTCBMML are found in the setting of cell‐mediated immunity, as well as in association with non‐alloimmune mechanisms. The available treatments for AMR and CMR are different, and it is important to ascertain the dominant mechanism when approaching an individual patient. At present, no gold standard exists to establish the specific pathogenesis in the more ambiguous cases. We detail here the differential diagnosis of MVI, TG, and PTCBMML.